2009
DOI: 10.1116/1.3245993
|View full text |Cite
|
Sign up to set email alerts
|

Double-anchoring fluorinated molecules for antiadhesion mold treatment in UV nanoimprint lithography

Abstract: In this work, the authors evaluate a new type of perfluoropolyether molecule ͑FLUOROLINK ® S10͒ to be used as an antisticking mold treatment in UV nanoimprint lithography. Unlike currently used ones, this molecule has two anchoring ends groups allowing two covalent grafting sites of the molecule to the mold surface. Obtained results on this molecule are compared to Optool DSX's ones. Using contact angle measurement, x-ray photoelectron spectroscopy, and electron spin resonance, the authors carried out chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…1, was selected for this study because it has a fairly large molecular weight (average = 1850 g/mol) compared to perfluoroalkylsilanes and two silane grafting end groups. Longer functional molecules have been shown to increase the hydropobic/ oleophobic character of films [26,29], and two grafted ends increases resistance to mechanical removal from the matrix [30]. Additionally, interchain hydrogen bonding between amide moieties has been found to enhance intermolecular stability [31][32][33].…”
Section: Preparationmentioning
confidence: 98%
See 1 more Smart Citation
“…1, was selected for this study because it has a fairly large molecular weight (average = 1850 g/mol) compared to perfluoroalkylsilanes and two silane grafting end groups. Longer functional molecules have been shown to increase the hydropobic/ oleophobic character of films [26,29], and two grafted ends increases resistance to mechanical removal from the matrix [30]. Additionally, interchain hydrogen bonding between amide moieties has been found to enhance intermolecular stability [31][32][33].…”
Section: Preparationmentioning
confidence: 98%
“…1. Chemical structure of Fluorolink S10, m/n = 1.5-2.5, 2 < n < 5, and 5 < m < 9 [30]. digital microscope and analyzed using the LB-ADSA method in the ''Drop Analysis'' plugin [34] for ImageJ.…”
Section: Characterizationmentioning
confidence: 99%
“…A flawless hexagonal A c c e p t e d M a n u s c r i p t 3 array of porous alumina on Si substrate can be obtained with a good reproducibility on very large surfaces [7]. However, despite a mold can be re-use a large number of time [14], the nanoimprint process is still restricted in surface by the time -and so the cost -required to produce large highresolution molds since they have to be made by electron beam lithography.…”
Section: Introductionmentioning
confidence: 98%
“…However, in 2007, Houle et al identified a premature degradation of their antisticking properties when imprinting into a vinyl-ether 5 or an acrylate-based 6 resist. By examining three different fluorinated antisticking layers ͑F-ASLs͒: Optool DSX, 1H ,1H ,2H ,2H-perfluoro-octyl-trimethoxysilane, 12 and Fluorolink S10 from Solvay-Solexis, 13 we have proven that, independent of the length and composition of the F-ASL molecules, a premature degradation of the F-ASL is always occurring after few tens of imprints into a free radical resist system. 6,9,10 In 2009, we demonstrated that it is possible to quantify the chemical interaction occurring at the mold/resist interface during UV exposure by using electron spin resonance ͑ESR͒.…”
Section: Introductionmentioning
confidence: 99%